Pheochromocytoma associated with a succinate dehydrogenase subunit B mutation: A minireview and a case report - Rezkallah Emad; Elsaify Andrew; Martin Victorino; Viva Laura; Nag Sath; Green Barnabas; Cheesman Matthew; Elsaify Wael (Endocrine Regulations, 2023)
Objective. Pheochromocytomas and paragangliomas are rare neuroendocrine tumors that arise from the chromaffin cells of the adrenal medulla or extra-adrenal tissues. These tumors are characterized by an excessive secretion of catecholamines, which are responsible for the clinical manifestation of the disease. Although most of these tumors are sporadic, underlying genetic abnormalities may be present in up to 24% of the cases. A succinate dehydrogenase subunit B (SDHB) mutation represents one of the rare presentations of the disease. In this study, we represent a rare case of pheochromocytoma associated with SDHB mutation.